Maritime-Continental Contrasts in the Properties of Low-Level Clouds: A Case Study of the Summer of the 2003 Yamase, Japan, Cloud Event - Nawo Eguchi; Tadahiro Hayasaka; Masahiro Sawada (Advances in Meteorology)
Satellite data were used to investigate maritime-continental differences in the characteristics of the low-level cloud (the Yamase cloud) that covered northeast Japan during the summer of 2003. The features of the Yamase cloud were found to be almost the same as those of general stratus clouds but with a smaller effective radius (re) and a greater optical thickness (τ) over land, as compared with general stratus clouds. The values of re over land (average, 11.8 μm) were smaller than those over the ocean (13.5 μm), and the values of τ and the cloud water path over land (20 and 145 gm−2, resp.) showed larger spatial variances than those over the ocean (10 and 86 gm−2, resp.), although the cloud top altitude was nearly the same over both ocean and land (1–3 km). We suggest that this maritime-continental contrast is a result of the combined effects of topography and aerosols characteristics. The Yamase wind blowing from the ocean is forced upwards in coastal regions by the steep mountainous terrain. The updraft drives the inhomogeneity in cloud parameters, and a convective-like cloud develops without precipitation. The relationship between re and τ suggests high aerosol concentrations and unstable conditions over land.